2020
DOI: 10.1037/tps0000257
|View full text |Cite
|
Sign up to set email alerts
|

Power and race in Black and White men’s perceptions and experiences of manhood.

Abstract: Traditional masculinity delineates a hegemonic set of beliefs and expectations about manhood in the United States that are most applicable to White men and marginalize men of color. In this study, we used an intersectional, qualitative framework to examine the role of race and power in shaping Black (n ϭ 11) and White (n ϭ 12) men's perceptions and experiences of manhood. Analysis of focus group data revealed two ways in which power was linked to manhood. First, men expressed that manhood was linked with respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…For example, interventions should be mindful of the complexity that boys and men harm through and are harmed by hegemonic masculinity as well as forces of oppression (Jewkes et al, 2015; Levant & Pryor, 2020). This highlights a need to balance accountability for men’s harmful behaviors with a trauma-informed approach that does not shame or ignore boys and men who are survivors of violence (Brush & Miller, 2019; Davies et al, 2010), as well as an intersectional lens that attends to power dynamics among boys and men, such as that of race (Brassel et al, 2020). While we consider healthy masculinities to be imperative, there is not one universal expression of healthy masculinity.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…For example, interventions should be mindful of the complexity that boys and men harm through and are harmed by hegemonic masculinity as well as forces of oppression (Jewkes et al, 2015; Levant & Pryor, 2020). This highlights a need to balance accountability for men’s harmful behaviors with a trauma-informed approach that does not shame or ignore boys and men who are survivors of violence (Brush & Miller, 2019; Davies et al, 2010), as well as an intersectional lens that attends to power dynamics among boys and men, such as that of race (Brassel et al, 2020). While we consider healthy masculinities to be imperative, there is not one universal expression of healthy masculinity.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…The acceptance of a dominant ideology from a position of power imposes norms, roles, expectations, and standards onto other groups in a position of less power. This first tenet of intersectionality iterates processes in which dominant ideologies contribute to multiple systems of oppression that are mutually interconnected in upholding one another to maintain social order within the larger matrix of domination (Brassel et al, 2020; Kaushik & Walsh, 2018; Wesp et al, 2018).…”
Section: A Critical Reflection Of Intersectionality Theorymentioning
confidence: 99%
“…The methodological diversity reflected in these projects is striking. Kilgore et al (2020); Brassel, Settles, et al (2020); and Singh and Bullock (2020) use critical qualitative methods to explore intersectionality in individual lives and cultural representation. Coles and Pasek (2020), Albuja al.…”
Section: Intersectional Psychology In "Revolting Times"mentioning
confidence: 99%
“…What does hegemonic masculinity look like in intersectional relief? Brassel, Settles, et al’s (2020) contribution to the special issue offers an answer to this question via qualitative examination of how racial power and privilege shape both Black and White men’s perceptions and experiences of manhood in the contemporary United States. Brassel and colleagues found that the intersection of race and gender actually produced different and similar experiences of manhood, once again reminding psychologists of Cole’s (2009) emphasis on continuities as well as divergences in the study of intersectional phenomena.…”
Section: The Contributions In the Special Issuementioning
confidence: 99%
See 1 more Smart Citation